GERAKAN TA'AWUN MUHAMMADIYAH: GERAKAN SOSIAL POLITIK ADILUHUNG - Muhammad Ridha; Firdaus Syam (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
This study discusses the manifestation of the value of ta'awun in the Muhammadiyah organization which has succeeded in bringing the Muhammadiyah Organization as one of the largest Islamic organizations in Indonesia with thousands of assets in the form of educational institutions, health institutions, social institutions and various other social institutions whose number continues to increase every year. Of course, making Muhammadiyah a community organization that has political bargaining power at the national level. This research uses the library research method, which is a research method whose data comes from various reading materials, including journals, books, and various other readings that are relevant to the title to be discussed. The result is that Muhammadiyah is able to become a political force that is respected by the central government because the political ta'awun movement is oriented towards high politics and ta'awun nationalism in the form of the theological manifestations of Al-Ma'un and Al'Asr and all within the framework of Muhammadiyah's view of Pancasila as Darul Ahdi Was Shahadah.